Comparison of the dynamics of light and color characteristics of compact fluorescent and led lamps in process of service life - Кожушко, Григорій Мефодійович; Басова, Юлія Олександрівна; Губа, Людмила Миколаївна (Technology audit and production reserves, 2016)
The results of the comparative study of light and color characteristics of compact fluorescent (CFL) and LED lamps in the process of service life are shown. It is shown that commercial samples of LED lamps, which come to the Ukrainian market, have an advantage over CFLs on service life, luminous efficiency, stability of light and color parameters in the process of service life. Lumen maintenance factor of the investigated CFL parties after 6000 hours is 77-62 %. CFLs color temperature in the process of service life is reduced for 6000 hours approximately 100-300 K for lamps with a color temperature of 2700-4000 K for the lamps of 13-32 Watt and 600-900 K color temperature of 6500 K for the lamp of 55-85 Watt. Lumen maintenance factor of the investigated parties of LED lamps after 6000 hours is 99-93 %. Deviation of the chromaticity coordinates of the initial value of 6000 hours no more than one degree of MacAdam ellipses. The color temperature is changed at the same time not more than 100 K. The cost of the light energy generated by modern light sources is calculated. Cost of light energy unit using LED lamps below, compared with CFL, about 1,3 times for electricity tariffs and prices for the lamps in Ukraine in May 2016.